Anticancer, antioxidant, and antibacterial activity of the medicinal orchid Dienia ophrydis (J. Koenig) Seidenf. - Tinoammini, Noyaljohnson; Aazhivaendhan, Gopalakrishnan; Maharaja, Somasundaram; Kumar, Thiruppathi Senthil (Journal of Phytology, 2025)
The terrestrial orchid Dienia ophrydis is valued for its therapeutic properties in the traditional folk medicine of China, Taiwan and Vietnam. The study aims to identify the potential biological activities from the whole-plant extract of D. ophrydis. Three solvents such as hexane, chloroform, and aqueous-ethanol were used for extraction. The anticancer, antioxidant, and antibacterial properties of these extracts were evaluated. The chloroform and aqueous-ethanol extracts were effective in inhibiting the cancer cell growth with IC50 values of 58.2 μg/mL and 43.08 μg/mL, respectively in MCF-7 cell line. The DPPH assay showed a maximum percentage of inhibition in aqueous-ethanol extract with 90.64%. The maximum zone of inhibition against Staphylococcus aureus and Escherichia coli was 13.10±0.35 mm and 14.05±0.85 mm. The findings support the pharmacological benefits of D. ophrydis and highlight its potential as a source of novel therapeutic agents.